URGENSI PENATAAN HUKUM KERUANGANGKASAAN DALAM KERANGKA KEPENTINGAN NASIONAL NEGARA BERKEMBANG - Agus Pramono (Masalah-Masalah Hukum, 2019)
The presence of  the space industry which sends to be dominated by private companies in developed countries has encouraged the need for developing country national legal framework thar are accomodative to regulate commercial space activities. On the other hand there are developing countries that have space activities and have national legal instruments, on the other there are developing countries that have just started space activities but do not have national legal instrument. Therefore, the arrangement of international and national legal instrument that regulate the interest of developing countries is urgent. In addition, this study show that existing legal transformation is not successful considering the transformation is not less attention to the full interest of the parties concerned.